2020
DOI: 10.1111/mcn.13020
|View full text |Cite
|
Sign up to set email alerts
|

High sugar content of European commercial baby foods and proposed updates to existing recommendations

Abstract: The aim was to determine whether commercial baby foods marketed within Europe (up to 36 months of age) have inappropriate formulation and high sugar content and to provide suggestions to update European regulations and recommendations as part of a nutrient profile model developed for this age group. The latter was produced following recommended World Health Organization (WHO) steps, including undertaking a rapid literature review. Packaging information from countries across the WHO European region was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
51
2
4

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 29 publications
10
51
2
4
Order By: Relevance
“…In the current study, 57.1% of ‘Baby biscuits and rusks’ and 29% of ‘Baby fruit products, desserts and yoghurts’ contained free sugars. Although the food categories do not correspond exactly, these findings are in line with those by Hutchinson et al [ 14 ] that found high levels of free sugars in ‘fruit purees (with cereal or milk)’ and ‘dry cereals (with high-protein foods)’. A German study that assessed commercial and home-made meals of 6–12-month-old infants found added sugars in less than a quarter of the meals [ 34 ].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…In the current study, 57.1% of ‘Baby biscuits and rusks’ and 29% of ‘Baby fruit products, desserts and yoghurts’ contained free sugars. Although the food categories do not correspond exactly, these findings are in line with those by Hutchinson et al [ 14 ] that found high levels of free sugars in ‘fruit purees (with cereal or milk)’ and ‘dry cereals (with high-protein foods)’. A German study that assessed commercial and home-made meals of 6–12-month-old infants found added sugars in less than a quarter of the meals [ 34 ].…”
Section: Discussionsupporting
confidence: 84%
“…Almost ¼ of the products listed a free sugar (as defined in [ 12 ]) as an ingredient. Hutchinson et al [ 14 ] reported that on average, between 21% (Denmark) to 58% (Hungary) of products listed an ‘added sugar’ (with a definition similar to ‘free sugars’ by [ 12 ]) as an ingredient. In the current study, 57.1% of ‘Baby biscuits and rusks’ and 29% of ‘Baby fruit products, desserts and yoghurts’ contained free sugars.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the first study to report the “free sugars” and “added sugars” content of commercial infant foods. The finding that pouches, on average, did not contain any free or added sugars was surprising, particularly given the widespread concern about high sugars content in pouches, and the emphasis being placed on the sugars content of commercial infant foods in the literature [ 8 , 28 , 43 ]. The WHO Regional Office for Europe made a call in 2019 to ban added sugars and “sweetening agents” (including fruit juices and fruit juice concentrates) in commercially available complementary foods [ 27 ].…”
Section: Discussionmentioning
confidence: 99%